Editorial - Braude, Stephen (Journal of Scientific Exploration, 2014)
I suppose most of us have wondered at one time or another whether a person’s apparently defining character traits are fixed, or whether people are capable of meaningful and deep change. Perhaps the issue arises most frequently in the context of intimate personal relationships, but it seems also to be a recurring topic of practical or professional concern to those studying scientific anomalies. I subscribe to several email listserves, one of which is a forum for psi researchers, and this topic routinely forms the background for discussion. It usually happens in the following way. First, some intransigent skeptic (or, perhaps more accurately, passionate psi-denier) publishes something outrageous (if not libelous) about a serious and diligent member of the parapsychological research community. It might be a severe blast of ad hominem attacks lacking even the appearance of empirical support. Or, it might be an ostensibly evidence-supported critique which only the well-informed would know to be inexcusably one-sided if not blatantly dishonest. The former happens frequently to Rupert Sheldrake. The latter is a specialty of career skeptics who posture as careful researchers themselves but who sedulously avoid discussing evidence that’s most difficult to explain away.1 When a new such attack surfaces, listserve members usually respond with a furious flurry of postings about how best to respond and whether to respond at all. A related manifestation of skeptical intransigence is the manner in which Wikipedia biographies of parapsychologists, LENR researchers, and others have been hijacked by a collection of Wikipedia insiders who have rewritten the biographies, replaced accurate information with falsehoods, and thwarted all attempts to correct the misrepresentations. Here, too, victims of this treatment wonder how—or whether there’s any point in even trying—to counter the damage.